KEEFEKTIFAN PENILAIAN KINERJA MODEL PEMBELAJARAN KOOPERATIF DENGAN METODE PENEMUAN PADA POKOK BAHASAN JAJARGENJANG DI KELAS VII - Faridah, Luluk (Jurnal Ilmiah AdMathEdu, 2012)
One the factor that effect to assessment the learning mathematics is assessment. Performance assessment is assessment that require students to demonstrate the performance, instead of answering of selecting an answer from a range of possible answer are already available. With the discovery method is no longer expected students to memorize formula or concept. But knowing how to get formula or concept through the patterns drawn by your self, so if the students forget, they can reconstruct these patterns and will obtain the required formula or concept. The discovery method combined with cooperative learning model is based on the theory that students will more easily find and understand difficult concept when using this learning model. This research is descriptive research that describes or explains the event. The research is done at SMPN 3 Taman Sidoarjo and the subject of the research is students of class VII B. In this research, the effectiveness of the learning implementation is based on: (1) completeness of learning results, (2) student activities, (3) teachers ability to manage learning, and (4) students response towards learning. The analysis showed the students complete the implementation of the study. The ability of teacher to manage students learning activies and shows effective. While the response of students in the teaching-learning shows possitive. Therefore, it can be concluded that the fourth aspect of the effectiveness of the learning achieved.   Key words: Effectiveness, Performance assessment, Cooperative, Discovery method.